CSL-independent Notch signalling: a checkpoint in cell fate decisions during development? - Martinez Arias, A.; Zecchini, V.; Brennan, K. (Current Opinion in Genetics and Development, 2002)
During development, signalling by members of the Notch family of cell surface receptors plays a widespread role in the assignation of cell fates within the process of lateral inhibition. This function of Notch is mediated by a well-established mechanism that relies on a ligand-induced release of the intracellular domain of Notch (NICD) and the interaction of this fragment with members of the CSL (CBF1, Suppressor of Hairless, Lag-1) family of transcription factors within the nucleus. However, there is increasing evidence that Notch can signal in CSL-independent modes.